2016
DOI: 10.3390/nu8100605
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Synbiotics in Patients with Slow Transit Constipation: A Prospective Randomized Trial

Abstract: Synbiotic intake may efficiently restore the balance of gut microbiota and improve gastrointestinal functions. The aim of the study was to evaluate the efficacy of a synbiotic in patients with slow transit constipation. A total of 100 patients with slow transit constipation were randomized to receive either a synbiotic or placebo twice daily for 12 weeks. The primary efficacy endpoints were the clinical remission and improvement rates at weeks 4 and 12. Stool frequency and consistency, colonic transit time (CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 38 publications
(56 reference statements)
1
41
0
Order By: Relevance
“…The benefits of pro, pre or synbiotic supplementation are known as beneficial to gut functionality. Studies similar to ours, in any way, have shown that probiotic intake (which are related to synbiotic) is capable of improving constipation in general population; the benefits pointed by the studies included increasing in the colonic transit (30) ; improvement in evacuation frequency (31) ; improvement in stool consistency (32) , among others. The benefits of these substances seem to be more pronounced when planned to specific groups, such as the ones diagnosed as functional constipation (33) .…”
Section: Discussionsupporting
confidence: 64%
“…The benefits of pro, pre or synbiotic supplementation are known as beneficial to gut functionality. Studies similar to ours, in any way, have shown that probiotic intake (which are related to synbiotic) is capable of improving constipation in general population; the benefits pointed by the studies included increasing in the colonic transit (30) ; improvement in evacuation frequency (31) ; improvement in stool consistency (32) , among others. The benefits of these substances seem to be more pronounced when planned to specific groups, such as the ones diagnosed as functional constipation (33) .…”
Section: Discussionsupporting
confidence: 64%
“…Subjects were predominantly female, mean age ranged from 22-50 years, and mean body mass index ranged from 19-32 kg/m 2 ( Table 1 ). A total of 19 studies [ 19 - 36 , 38 ] with 20 comparisons contributed data for stool frequency and 8 studies [ 18 , 21 , 25 , 26 , 30 - 32 , 37 ] with 9 comparisons contributed data for ITT. Intestinal transit time was reported as total intestinal transit time using radiopaque markers in 3 studies, colonic transit time using radiopaque markers in 3 studies, whole gut transit time using radiopaque markers in 2 studies, and orocecal transit time using carmine red dye in 1 study.…”
Section: Resultsmentioning
confidence: 99%
“…That this study was unsuccessful may feasibly be due to subject heterogeneity in the most bothersome symptom. We used modified Rome III diagnostic criteria for chronic functional constipation as inclusion conditions, and to limit the severity to those with mild to moderate constipation a CCCS score of 8–20 was set, as used elsewhere [ 59 , 60 , 61 ]. At baseline, the groups were well balanced, although compared to the placebo group, the 12 g/day dose polydextrose group had a slightly higher, albeit statistically non-significant, age (median 47 year vs. placebo 31 year, p = 0.11) and slightly lower daily intake of fiber (14.2 vs. placebo 15.3 g/day, p = 0.052).…”
Section: Discussionmentioning
confidence: 99%